Developmental Abnormalities of the Thymus in hea/hea Mutant Mice - SHIMIZU, Koji; KASAHARA, Yuki; KURIBAYASHI, Koichi (Experimental Animals, 2008)
This study found that the thymus of hea/hea mutant mice (hea mice) became atrophic in early phase of life and that the differentiation of CD4-CD8- (Double Negative; DN) into CD4+CD8+ (Double Positive; DP) cells during the development of T cells in the thymus was abnormal. The thymus development of hea mice was different from that of normal littermates. After 6 days of age, the numbers of thymocytes in hea mice decreased. The total numbers of DP cells in the thymus of hea mice reached the maximum at 6-9 days of age and then decreased after 10 days. The total numbers of DN cells in the thymus were almost constant in hea mice and normal littermates. These results indicate abnormalities in the process of differentiation from DN to DP cells in the thymus of hea mice. Flow cytometoric analysis indicated the presence of a large number of apoptotic and necrotic cells in the thymus of 13-15-day-old hea mice. However, there were no significant differences in the amount of mRNAs of Fas, Fas ligand and IL-7 between hea mice and normal littermates. Splenocytes from hea mice produced the same amount of cytokine mRNAs as normal littermate mice and the hea mutation (Ttc7(fsn-hea)) did not affect serum levels of IgM immunoglobulin. However, activated T cells from hea mice showed more secretion of cytokines derived from Th2 cells than from Th1 cells, so they might be affected by abnormalities of the immune system.